Effects of sulfasalazine and tofacitinib on the protein profile of articular chondrocytes. Issue 5 (September 2014) - Endo, Wataru; Arito, Mitsumi; Sato, Toshiyuki; Kurokawa, Manae S.; Omoteyama, Kazuki; Iizuka, Nobuko; Okamoto, Kazuki; Suematsu, Naoya; Nakamura, Hiroshi; Beppu, Moroe; Kato, Tomohiro
Abstract Objective. Sulfasalazine (SSZ) and tofacitinib are effective for treating rheumatoid arthritis, however, their effects on chondrocytes have not been fully understood. We here tried to elucidate their effects on chondrocyte proteins. Methods. We treated chondrocytes from five osteoarthritis patients with IL-1β, IL-1β+ SSZ, IL-1β+ tofacitinib, SSZ alone, and tofacitinib alone. Then, we compared protein profiles of the chondrocytes using two-dimensional differential gel electrophoresis. Further, we identified altered proteins by mass spectrometry. Results. Out of 892 detected protein spots, the IL-1β stimulation changed intensity of 43 spots more than 1.3-fold or less than 1/1.3-fold significantly. SSZ suppressed the IL-1β-induced intensity alteration in 16 (37%) out of the 43 protein spots. Tofacitinib suppressed the IL-1β-induced alteration in 4 (9.3%) out of the 43 spots. The production of AMP deaminase 2 and procollagen-lysine, 2-oxoglutarate 5-dioxygenase 2 were increased by IL-1β and the increase was suppressed by SSZ and by tofacitinib. SSZ alone altered intensity of 273 (31%) out of the 852 spots significantly, whereas tofacitinib alone altered intensity of only 24 (2.7%) out of them. Conclusion. SSZ and, to lesser extent, tofacitinib suppress the effects of IL-1β on the protein profiles of chondrocytes. Our data would promote understanding of effects of the drugs on chondrocytes.